2015
DOI: 10.3389/fpsyg.2015.01059
|View full text |Cite
|
Sign up to set email alerts
|

Calm and smart? A selective review of meditation effects on decision making

Abstract: Over the past two decades, there has been a growing interest in the use of meditation to improve cognitive performance, emotional balance, and well-being. As a consequence, research into the psychological effects and neural mechanisms of meditation has been accumulating. Whether and how meditation affects decision making is not yet clear. Here, we review evidence from behavioral and neuroimaging studies and summarize the effects of meditation on social and non-social economic decision making. Research suggests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 95 publications
(106 reference statements)
0
27
0
Order By: Relevance
“…Meditation has a wide range of types such as loving kindness meditation (taught by spiritual leaders or experts versed in the Buddhist tradition, focused on silent repetition of phrases based on Buddhist teachings, and incorporated into holistic health and group support programs) and mindfulness meditation (increasingly taught by trained clinical psychologists, focused on emotional self-regulation and focusing attention, and incorporated into cognitive therapy and clinical care). Meditation both over short-term and long-term has been found to improve cognition [20][21][22] . One study of 54 college students in Singapore playing the Dictator Game (where the Dictator, player A, divides money provided by the experimenter between what she wants to keep for herself and what she wants to give away to an anonymous player B) reported that loving kindness meditation led to higher cooperation 23 .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Meditation has a wide range of types such as loving kindness meditation (taught by spiritual leaders or experts versed in the Buddhist tradition, focused on silent repetition of phrases based on Buddhist teachings, and incorporated into holistic health and group support programs) and mindfulness meditation (increasingly taught by trained clinical psychologists, focused on emotional self-regulation and focusing attention, and incorporated into cognitive therapy and clinical care). Meditation both over short-term and long-term has been found to improve cognition [20][21][22] . One study of 54 college students in Singapore playing the Dictator Game (where the Dictator, player A, divides money provided by the experimenter between what she wants to keep for herself and what she wants to give away to an anonymous player B) reported that loving kindness meditation led to higher cooperation 23 .…”
mentioning
confidence: 99%
“…Mindfulness meditation emphasizes non-judgmental attention to experiences in the present moment 24 . Meditation practices mainly modulate brain activities responsible for cognitive control, emotion regulation, and empathy, each of which is associated with specific brain areas including the anterior cingulate cortex (ACC), insula, and amygdala [25][26][27][28] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These relational concepts are also of central importance in the FOC Framework (Feo et al., ). In addition, meditation‐fostered calmness is linked to improved thinking and decision‐making ability (Sun, Yao, Wei, & Yu, ) and could also enhance nurses’ intellectual engagement, critical thinking and attention to patient safety issues. In an interesting divergence, the FOC Framework's relationship established concepts focus on patients’ meaningful experience of care provided by nurses while the TM concepts focus on nurses’ capacity to establish meaningful relationships with patients.…”
Section: The Capacity Of Careful Nursing To Address Fundamental Carementioning
confidence: 99%
“…Meditation, as conscious training of attention aimed at modifying mental processes to enhance mental wellbeing (Walsh and Vaughan 1980), modulates brain activities associated with cognitive control, emotion regulation, and empathy to improve individual decision-making (Sun et al 2015). In addition, by strengthening mental flexibility (Bauer-Wu 2010) and consciousness in decision-making (Nash and Newberg 2013), meditation influences individual decision-making styles (McNaughton 2003).…”
Section: Introductionmentioning
confidence: 99%